This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Rearranging, we have
3 1 × 9 x + 2 + 2 1 × 9 x + 1 = 6 × 4 x + 1 − 3 × 4 x
9 x + 1 ( 3 1 × 9 + 2 1 ) = 4 x ( 6 × 4 − 3 )
9 x + 1 × 2 7 = 4 x × 2 1
9 x + 1 = 4 x × 6
Rewriting in terms of powers of 2 and 3 , this is
3 2 x + 2 = 2 2 x × 6
and finally 3 2 x + 1 = 2 2 x + 1
The only way for both of these quantities to be equal is if the exponents on both sides are zero - ie if 2 x + 1 = 0 ; so the required answer is x = − 0 . 5 .